Current Status of Methane Emission Detection and Accounting in Oil and Gas Production Process Using AI Technologies - Liu, Yi (Journal of Theory and Practice of Management Science, 2025)
This paper explores the monitoring and accounting of methane escape emission in the process of oil and gas production. In the actual exploration, the monitoring and accounting methods of methane escape emission from oil and gas are firstly described. Then, the international analysis of methane gas escape emission, detection of methane gas escape emission in our country, accounting of methane gas emission in our country, regional characteristics and historical changes of methane gas escape emission in our country are analyzed in order to improve the emission quality.